'Insighters': the complexity of qualitative methods in youth music research. (3rd July 2021) - Sharp, Megan
ABSTRACT: In this article, I sketch out the rationale for utilising a reflexive and intersectional 'insighter' ethnography in youth research. I argue that because of the dynamic and complex nature of a youth music field such as punk, enquiry into young people's scenes and spaces requires rigorous consideration at the beginning, middle and end stages of research. I understand such a methodology to be an ongoing reflexive dialogue, one that continues in the 'writing up' phase. Using the example of queer punx, I explain the selection of a semi-structured interview format, participant observation and ethnographic framework for data collection. Furthermore, I suggest that an insider position to the research group might be better reconceptualised through the term 'insighter'. That term locates the researcher in a more flexible position between absolute insider and academic interpreter of data. Taking up an insighter position on the queer punx project afforded rich possibilities which would have been unachievable for an outsider or a pure insider researcher. Yet the 'insighter' position requires ongoing reflexive boundary work to negotiate the complex meaning of being inside as an academic researcher.